Motivational Factors and Challenges in Managing Record for Mobile Work - Atiqaf Mahathir, Nur; Kamaruddin Kadir, Irwan; Ahmad, Masitah; Norolazmi, Noorzeelawati; Imana Harun, Zakira; Mohammad Mobin, Noorsyahirah; Ridwan Seman Kamarulzaman, Mohd (International Journal of Engineering and Technology, 2018)
Mobile work is not a new phenomenon, but it is a result of better record-keeping records management. Apart from the development of electronic records and record-keeping systems, the practice of these functions continues to be office and paper-based and has supposedly been digitized. Mobile devices and online connections have enabled record creation beyond the office context, on other premises. The several of format in information management created challenges for preservation, until the point when a few researchers called it 'digital archaeology'. Mobile workers did their task in changing and unpredictable areas. Handling of records and document management was either straightforwardly in work situation or as soon as possible after the working hours. It may have implied working while at the same time going, at home or in different places, for example, while going to meeting or courses and customers' premises. Record management was important because it is often necessary to measures the importance areas in the organization. It is also to guarantee their continuity even if individual or that individual might leave the organization. In this issues, when we work as a team example for same related project and all of our colleagues will need the up to date documentation and also records related to their task. They also will share all the information regularly.